Fluency and the integration of semiotic resources in interactional learning processes. Issue 2 (4th May 2017) - Kern, Friederike; Ohlhus, Sören
Abstract: Fluency plays an important and largely unreflected role as a diagnostic tool in learning interactions. In our paper, we present a case study of videographed remedial lessons in mathematics, addressing the question of how useful the concept of fluency is for a description of learning as an observable and accountable interactive process. The concept of fluency in discourse and specifically in learning interactions is discussed and elaborated on the basis of our findings. In the reconstruction of interactive learning processes, fluency proves to be a phenomenon towards which both tutors and pupils orient themselves, while relying on different aspects of fluency in their coordinated effort to establish a global schema of calculation steps. In addition, fluency can provide a window on the progressive nature of a longitudinal learning process. As the pupil's performance of the technique to be learned becomes more and more fluent, this can serve as an indication of the planning processes involved, allowing for a more integrated realisation of the practice. This integration can be made clear by examining different aspects of interactive, multimodal and linguistic fluency.